ANALISIS EFISIENSI KEUNTUNGAN USAHATANI PADI SAWAH DENGAN TEKNIK TANAM PINDAH DAN TEKNIK TANAM BENIH LANGSUNG DI KAMPUNG ALUE JANGAT KECAMATAN DARUL IHSAN KABUPATEN ACEH TIMUR - Aminah Aminah; Devi Andriyani (Jurnal Ekonomi Pertanian Unimal, 2020)
This study aims to analyze the profit efficiency of rice farming using transplanting techniques and direct seed planting techniques in Alue Jangat, Darul Ihsan sub-district, East Aceh Regency. This study used primary data obtained directly from 5 rice farmers using transplanting techniques and 5 rice farmers using direct seed planting techniques in Alue Jangat, Darul Ihsan sub-district, East Aceh Regency during one planting period. The variables used are capital, labor, and planting time as inputs and the profits obtained by farmers as output. This study uses the Data Envelopment Analysis (DEA) method with the output-oriented Variable Return to Scale (VRS) approach. Rice farmers who use two planting techniques show that rice farmers obtain more efficient profit values by applying the TABELA technique compared to the TAPIN technique. There are 4 rice farmers who use direct seed planting techniques, and only 2 rice farmers using the transplanting technique obtain efficient scale value against the profits, while rice farmers using the TABELA technique show that 3 TAPIN rice farmers do not achieve an efficient value on the profits.